Para além do estado da Paraíba: direito animal e o transfederalismo brasileiro - Silva, Priscilla (2024)
The normative sources of Animal Law are essentially regional and municipal laws. Among these, the Paraíba Animal Law and Welfare Code stands out because, through article 225, §1, VII, of the 1988 Federal Constitution, recognized animals as subjects of rights and presented a catalog of rights, making it the most advanced animal law in Brazil. However, although the Code confirms the strengthening of cooperative federalism, the protection of non-human animals has still been disharmonious due to the absence of a federal law. Therefore, by identifying the transcendence of the fundamental right of non-human animals to a dignified existence, this research raised the following question: to standardize the normative sources of Animal Law in Brazil, is it possible to apply the Paraíba Animal Law and Welfare Code in other states? Given how complex contemporary times are, the research used the systemic-complex approach method and, to choose Paraíba’s law as a paradigm, it employed the comparative method as a procedure. Furthermore, the research adopted the analysis of books, scientific articles, case laws, and legislation as a technique. We concluded that federalism, in its traditional view, has not solved the problem arising from the lack of federal legislation governing the rights of non-human animals. Thus, through transfederalism, a concept proposed by José Arthur Castillo de Macedo, we identified that Paraíba’s law has been applied in jurisdictions other than the one corresponding to the state, leading to the standardization of the normative sources of Animal Law in Brazil.